(untitled) (ModaPalavra e-periódico, 2018)
This is an interview with Sabina Deweik, coolhunterand specializes in capturing social changes, in whichthe interviewee said about the research methodology of coolhunting, consumer behavior research and about how companies can benefit from this expert advice. Sabina also said her professional trajectory and how has moved to the trend research area, becoming precursor of coolhunting in Brazil in 2000’s, pointing out which the main difficulties faced in the beginning of the career, as well as what are the attributions necessary for the professional coolhunter. Finalized talking about the Zeitgeist (Spirit of the Times) current of society and the prospect of emerging social movements.